2019
DOI: 10.1002/cam4.2774
|View full text |Cite
|
Sign up to set email alerts
|

Identification of prognostic genes in adrenocortical carcinoma microenvironment based on bioinformatic methods

Abstract: Background:To identify prognostic genes which were associated with adrenocortical carcinoma (ACC) tumor microenvironment (TME). Methods and materials: Transcriptome profiles and clinical data of ACC samples were collected from The Cancer Genome Atlas (TCGA) database. We use ESTIMATE (estimation of stromal and Immune cells in malignant tumor tissues using expression data) algorithm to calculate immune scores, stromal scores and estimate scores.Heatmap and volcano plots were applied for differential analysis. Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 43 publications
3
38
0
Order By: Relevance
“…Taken together, our results suggest that the enriched immune cells might play a crucial role in the development of CM and thus may represent potential therapeutic targets for a specific anti-tumor immune response. Additionally, the present study revealed that CM with systemic metastases had significantly lower immune scores than non-metastatic tumors, a finding that has previously been reported for different cancer types 27,28 . In a study of Mlecnik et al 27 , a low immune score was associated with an increased risk of systematic metastases in patients with colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, our results suggest that the enriched immune cells might play a crucial role in the development of CM and thus may represent potential therapeutic targets for a specific anti-tumor immune response. Additionally, the present study revealed that CM with systemic metastases had significantly lower immune scores than non-metastatic tumors, a finding that has previously been reported for different cancer types 27,28 . In a study of Mlecnik et al 27 , a low immune score was associated with an increased risk of systematic metastases in patients with colorectal cancer.…”
Section: Discussionsupporting
confidence: 89%
“…Initial data have been in favor of its use [71][72][73]; however, this tool is not prospectively validated, which limits its use in clinical practice. Based on the data we have regarding genetic markers in patients with ACC [41][42][43]74], using genetic profiling to predict recurrence risk is another important tool. It has been used successfully as a prognostic marker in other malignancies, including breast cancer [75]; however, studies are needed to prospectively validate its use for ACC.…”
Section: Future Directionsmentioning
confidence: 99%
“…To provide more precise prediction of individualized outcomes, future survival estimates have to be based on a better understanding of the biology of ACC. Pangenomic studies (transcriptome, methylome, chromosome alteration, and mutational profiles) can provide discriminant prognostic models for localized ACC 31 , 32 , and genes associated with prognosis in the ACC tumour microenvironment are also valuable 33 . Such techniques are unlikely to become part of routine clinical practice soon and, until the results of such genomic tests can be integrated in this way, risk stratification based on easily accessible parameters remains paramount.…”
Section: Discussionmentioning
confidence: 99%